Collaboration in demand chain: a systematic review from a communication perspective - Qiao, Hong (Cranfield University, 2004)
Collaboration is imperative in the demand chain in order to be able to share the seamless transparent information which is one of the key principals of demand chain organisations (Lee and Whang, 2001). It has been a key enabler widely accepted in demand chain literature, but most of the authors do not scientifically justify it. Since demand chain management is an emerging field of interest for academics, how collaboration works in this particular environment understandably remains under-researched. Most research on collaboration between buyer and supplier is not explicitly conducted in the competitive environment. This thesis, using the methodology of systematic review, investigates the literature of dem and chain management and collaboration from a communication perspective. The review of studies on collaboration between buyer and supplier is expected to provide insight for the study on collaboration in demand chain environment. There are 21 works included for the demand chain literature review and 25 for collaboration from a communication perspective. This systematic review of literature on demand chain management and collaboration from a communication perspective identifies seven enablers for demand chain system, among which collaboration and technology-enabled communication are two key enablers together with agility etc. This review also identifies two main themes in collaboration with communication perspective literature: communication in collaboration with buyer-supplier relationships as a communication media, and communication in collaboration with buy-supplier relationships as a social process. A holistic view of communication behaviour within buyer-supplier relationships is recommended and future work in this field is needed.